The role of work stress on individual work performance: Study in civil servants - Novika Grasiaswaty (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2020)
This study wanted to see the role of work stress of three kinds of individual work performance (task performance, contextual performance, and counterproductive work behavior). Previous researches showed different kind of performance related with different work stresses. The study was conducted on 83 civil servants in one work unit in Jakarta. Data were analyzed by using Lavaan in R program. The results showed that ‘control’ and ‘support colleagues was significantly affected task and contextual performance. While for counterproductive work behavior, ‘role’ and ‘change’ had positive impact of the behavior. These results indicate that different work performance is related to different types of work stress. Further result and implication were discussed.